Penerapan Kearifan Lokal Pada Usaha Tani Padi Di Kelurahan Deri Kecamatan Sesean Kabupaten Toraja Utara - Werang, Michael Macmarten Koda; Azuz, Faidah; Salam, Suryawati (PALLANGGA: Journal of Agriculture Science and Research, 2025)
Due to the changing times, local wisdom in each region began to fade, but in Deri Village, the farming community still practices or upholds local wisdom in rice farming. This study aims to determine the practical use of this local wisdom in rice farming in Deri Village, Sesean Sub-district, North Toraja Regency. North Toraja Regency. This study aims to determine the practical use of local wisdom in rice farming activities in Deri Village, Sesean Sub-district, North Toraja Regency. This research was conducted in Deri Village, Sesean Sub-district, North Toraja Regency. The informants in this study were determined as many as 15 people consisting of traditional leaders and religious leaders. The data analysis method used in this research is qualitative analysis method. The results showed that the farming community in Deri Village applies local wisdom in rice farming which includes four stages, namely; (1) Pre-Planting Stage which includes:  Ceremony to determine the time to go down the rice field (Medatu) and Ceremony to go down the rice field (Ma' Rara Kalo'); (2) Planting Stage which includes: Making a seeding place (Massukbak Panta'nakan), Planting Rice (Mantanan Pare), Fertilizing and Pest Management; (3) Harvest Stage which includes: Harvesting ceremony (Ma' Rakan for Aluk Todolo) and Rice Harvesting (Mepare); (4) Post-harvesting stage includes: Results and Harvest Thanksgiving. These activities are a form of culture or local wisdom in cultivating paddy rice in Deri Village which is still applied today. The figures involved or play an important role in every implementation of traditional ceremonies or rituals in the application of local wisdom in rice farming in Deri Village, namely: (1). Parandangan Ada' (Customary Leader); (2). Tomina (Prayers); and (3). The local community (both from children to adults/parents). Seiring perkembangan zaman kearifan lokal di setiap daerah mulai memudar, namun di Kelurahan Deri masyarakat petani masih menerapkan atau memegang teguh kearifan lokal dalam berusahatani padi. Penelitian ini bertujuan untuk mengetahui penerapan kearifan lokal setempat dalam usahatani padi di Kelurahan Deri Kecamatan Sesean Kabupaten Toraja Utara. Penelitian ini dilakukan di Kelurahan Deri Kecamatan Sesean Kabupaten Toraja Utara. Sampel atau informan dalam penelitian ini sebanyak 15 orang yang terdiri dari ketua adat dan pemuka agama. Metode analisis data yang digunakan dalam penelitian ini yaitu metode analisis kualitatif. Hasil penelitian menunjukkan bahwa masyarakat petani di Kelurahan Deri menerapkan kearifan lokal dalam berusahatani padi yang meliputi empat tahap, yaitu;  (1) Tahap pra tanam yang meliputi:  upacara waktu penentuan turun sawah (Medatu) dan upacara turun sawah (Ma’ Rara Kalo’); (2) Tahap penanaman  yang meliputi: membuat tempat pembenihan (Massukbak Panta’nakan), menanam padi (Mantanan Pare), pemupukan  dan penanganan hama; (3) Tahap panen yang meliputi: upacara penentuan panen (Ma’ Rakan untuk Aluk Todolo) dan panen padi (Mepare); (4) Tahap pasca panen meliputi: hasil dan syukuran panen. Berbagai kegiatan tersebut sebagai bentuk kebudayaan atau kearifan lokal dalam berusahatani padi sawah di Kelurahan Deri yang masih di terapkan sampai sekarang. Tokoh-tokoh yang terlibat atau berperan penting dalam setiap pelaksaan kegiatan upacara atau ritual adat dalam penerapan kearifan lokal pada usahatani padi di Kelurahan Deri yaitu: (1). Parandangan Ada’ (Ketua Adat); (2). Tomina (Pendoa); dan (3). Masyarakat setempat (baik itu dari anak-anak sampai dewasa/orang tua).